Teorie a praxe výchovy k požární ochraně a ochraně obyvatelstva na základních školách - Vybíralová, Zuzana (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2009)
Theoretical basis is compiled (laws, notices, projects). Detailed description of preventive educational activity in fire prevention and civic defense in basic schools project Hasík is given. Improvements in children's knowledge level after introducing the project into education system are assessed. Further improvements are suggested.
Keywords: Hasík Project; ochrana obyvatelstva; preventivně výchovná činnost; požární ochrana; fire prevention; preventive education; projekt Hasík; Civic defense